Ultrastable Silicon Anode by Three-Dimensional Nanoarchitecture Design - Huang, Gang; Han, Jiuhui; Lu, Zhen; Wei, Daixiu; Kashani, Hamzeh; Watanabe, Kentaro; Chen, Mingwei (ACS nano, 2020)
State-of-the-art carbonaceous anodes are approaching their achievable performance limit in Li-ion batteries (LIBs). Silicon has been recognized as one of the most promising anodes for next-generation LIBs because of its advantageous specific capacity and secure working potential. However, the practical implementation of silicon anodes needs to overcome the challenges of substantial volume changes, intrinsic low conductivity, and unstable solid electrolyte interphase (SEI) films. Here, we report an inventive design of a sandwich N-doped graphene@Si@hybrid silicate anode with bicontinuous porous nanoarchitecture, which is expected to simultaneously conquer all these critical issues. In the ingeniously designed hybrid Si anode, the nanoporous N-doped graphene acts as a flexible and conductive support and the amorphous hybrid silicate coating enhances the robustness and suppleness of the electrode and facilitates the formation of stable SEI films. This binder-free and stackable hybrid electrode achieves excellent rate capability and cycling performance (817 mAh/g at 5 C for 10 000 cycles). Paired with LiFePO4 cathodes, more than 100 stable cycles can be readily realized in full batteries.